Partial recovery of microbiomes after antibiotic treatment. (2nd September 2016) - Raymond, Frédéric; Déraspe, Maxime; Boissinot, Maurice; Bergeron, Michel G.; Corbeil, Jacques
ABSTRACT: Antibiotics profoundly affect the gut microbiome and modulate microbial communities. We recently observed that antimicrobial drugs also impact the abundance and distribution of antibiotic resistance genes. In this addendum, we reanalyze our ∼1 trillion nucleotide shotgun metagenomic dataset to quantify comprehensive genomic differences at the sequence level before and after antibiotic treatment. We show that 7 day exposure to cefprozil leads to a statistically significant loss of metagenome sequences. Recovery of gut microbiomes 3 months after antibiotherapy was characterized by the emergence of new genome sequences not observed prior to antibiotic exposure. Participants with low initial gut microbiome diversity had an increased amount of sequences related to antibiotic resistance. Therefore, we suggest that while the taxonomical composition of microbiomes is partially affected by the antibiotic, the genomic content and population structure of bacterial communities is noticeably impacted.